35.9k views
1 vote
X^2(x+2)(x+6)=0
What are the solutions to the equation?

2 Answers

11 votes

Answer:

3 solutions

Explanation:

x = 0; x = 2; x = -6

User Gavilan Comun
by
4.9k points
3 votes

As we are given with an equation as follows :


{:\implies \quad \sf x^(2)(x+2)(x+6)=0}

As product of these three factors is equal . So , any of these factor can be 0 as product is 0 only when one of the expressions which are multiplied is 0. So , 3 cases arises as follows ;

Case I :-


{:\implies \quad \sf x^(2)=0}

On raising ½ power to both sides we have ;


{:\implies \quad \sf x=\pm \: 0}

Now , as +0 and -0 have no difference in them . So , it's simply 0


{:\implies \quad \sf So\quad x=0}

Case II :-


{:\implies \quad \sf x+2=0}


{:\implies \quad \sf So\quad x=-2}

Case III :-


{:\implies \quad \sf x+6=0}


{:\implies \quad \sf So\quad x=-6}


{:\implies \quad \bf \therefore \quad \underline{\underline{Hence \:\: x\in \{0,\: -6,\: -2\}}}}

User Mmmeff
by
4.9k points